Ethics in Muslim writing and research methodology: the case Ibn Khaldun’s scholarly writing - Salah, Machouche; Bensaid, Benaouda (Department of Islamic History and Civilization, Academy of Islamic Studies, University of Malaya, 2022)
This study examines the concept and practice of scholarly writing among Muslim scholars, with a special reference to ‘Abdul Rahman Ibn Khaldun (d.1406). The research draws on a textual analysis of Ibn Khaldun’s Muqaddimah and other early Muslim works regarding the craft of writing while addressing the broader,wider context of writing ethicality and its influence on social consciousness. This study discusses the worldview and ethics of writing, concepts,and terminologies, sources and objectives, investigation, and styles of presentation according. This research demonstrates that Ibn Khaldun’s writing methodology and style continue to stand as a prime example for scholarship in the social sciences and that his spiritual beliefs and value system served to further enhance the originality and rigor of his writing and conceptual schemes. Further researchacross a larger body of Muslim literature will bring about interesting insights on the relationship between spirituality and research writing, as well as the historical contribution of Muslim authors to the advancement of universal knowledge